Economic cost and efficiency analysis of a lithium-ion battery pack with the circular and elliptical cavities filled with phase change materials. (15th August 2022) - Tian, Man-Wen; Smaisim, Ghassan Fadhil; Yan, Shu-Rong; Sajadi, S. Mohammad; Mahmoud, Mustafa Z.; Aybar, Hikmet Ş.; Abed, Azher M.
Abstract: In this work, a battery pack (BAPA) containing 21 cylindrical battery cells was investigated. Active and passive approaches are used to regulate the battery's thermal management (THM). An enclosure packed with phase change material (PCM) surrounding the battery is employed for passive heat control. For the active method, forced airflow is utilized. PCM enclosure has two shapes of circular and elliptical, in which paraffin is used. In the active method, air flows into the BAPA at the velocity range of 0.0005 to 0.002 m/s. An economic analysis is performed for the electricity cost of the active method for several European countries. Battery temperature (T-B), pressure drop (PDP) in the BAPA at different air velocities, and two different shapes of the PCM enclosure are evaluated. The FEM is used for simulations. The results reveal that the use of an elliptical enclosure increases the maximum temperature (T-Mx) and average temperature (T-Av) of the battery and the amount of molten PCM also enhances compared to the circular enclosure. Also, the amount of PDP and power cost in the elliptical enclosure is more than that in the circular one. By increasing the velocity, the active technique decreases the amount of T-B while also increasing the amount of PDP and power cost. Highlights: Active and passive approaches are used to regulate the battery's thermal management. PCM enclosure has two shapes of circular and elliptical, in which paraffin is used. Using an elliptical enclosure increases maximum and average temperatures of battery. The amount of power cost in the elliptical enclosure is more than that in the circular one.